Weight Gain and Feed Conversion of Broiler Chickens in Reviewed from Cage Temperature and Humidity - Himatul Oktavia; Siti Eliana Rochmi; Tri Wahyu Suprayogi; Djoko Legowo (Journal of Applied Veterinary Science And Technology, 2021)
Background: Broiler chicken production is influenced by several factors, namely genetic, management, and environmental factors. Genetically superior chickens will not produce maximum results if not supported by a comfortable environment for chickens (comfort zone) because they are animals that will grow optimally at a certain temperature range. in addition, humidity also affects the production and health of chickens. So that the selection of the cage becomes important to create comfortable environmental conditions for chickens. Cage with a relatively stable temperature will greatly affect the production results, including body weight and feed conversion. Purpose: To determine the effect of temperature and humidity of semi-enclosed cages on weight gain and feed conversion of broiler chicken. Method: Observation was carried out during a period of maintenance of broiler chickens on farms and data collected in the form of the recording of chicken weight and feed conversion. Result: Temperature and humidity of semi-enclosed cages have a good effect on production results, with chicken harvest weight of 2197.3 grams and feed conversion of 1.52 kg. Conclusion: this study indicate that temperature and humidity have a good influence on weight gain of chickens and feed conversion value.